Economic Analysis of Cost and Returns of Milk Production, Extent of Adoption of Recommended Management Practices on Sample Dairy Farms in Bikaner District of Rajasthan (Global Journal of Science Frontier Research, 2014)
An economic analysis of sample Dairy farms has been presented through studying their costs and returns. The average cost of production per litre milk was ` 14.27 and the average net return per litre of milk was ` 8.28. The input-output ratio was worked out 1.58 at overall level. The cost C was ` 1867599.61 per dairy farm and 333449.99 per milch animal and the net income was` 1053011.60 per dairy farm and ` 18803.77 per animal. It was 10.50 litre, 11.53 and 15.80 litre for buffalo, Jersey cow and Holstein Friesian cow, respectively. In term of milk production as well as production traits, the Holstein Friesian and Jersey cows were more superior to buffaloes and local cows. Average milk production per lactation was ` 129374 liters per dairy farm and 4173 liters per animals. Out of total milk production, 7.47 per cent was consumed as fluid milk and 7.79 per cent used in processing for ghee, Dahi at home and remaining 84.74 per cent milk was sold as fluid milk. In general, 9.96 per cent milk was sold to the consumers directly, 19.35 per cent to the Hotel/Halwaies and 70.69 per cent milk was sold to the dairy plants.
Keywords: average cost; average net return; net income; lactation; consumers and adoption etc